A nexus of plate interaction: Vertical deformation of Holocene wave-built terraces on the Kamchatsky Peninsula (Kamchatka, Russia) - Pinegina T.K.; Bourgeois J.; Kravchunovskaya E.A.; Lander A.V.; Arcos E.M.; Pedoja K.; MacInnes B.T. (Geological Society of America Bulletin, 2013)
Kamchatsky Peninsula lies within a complex meeting place of tectonic plates, in particular, the orthogonal interaction of the west-moving Komandorsky Island block with mainland Kamchatka. Examining the Holocene history of vertical deformation of marine wave-built terraces along the peninsular coast, we differentiated tectonic blocks undergoing uplift and tilting separated by zones of stable or subsided shorelines. We analyzed ~200 excavations along >30 coastal profi les and quantifi ed vertical deformation on single profi les as well as along the coast using paleoshorelines dated with marker tephras. For the past ~2000 yr, the average rates of vertical deformation range from about –1 to +7 mm/yr. Uplift patterns are similar to those detected from historical leveling and from mapping of the stage 5e Quaternary marine terrace (ca. 120 ka). Average vertical deformation in the Holocene is highest for the shortest studied time period, from ca. A.D. 250 to 600, and it is several times faster than rates for marine oxygen isotope stage (MIS) 5e terraces. Vertical displacements observed along the coast are most likely coseismic and probably have included subsidence as well as uplift events. Because subsidence is generally associated with erosion, almost surely more prehistoric large earthquakes occurred than are recorded as topographic steps in these terraces. We suggest that the distribution of coastal uplift and subsidence observed along the Kamchatsky Peninsula coastline is qualitatively explained by the squeezing of the Kamchatsky Peninsula block between the Bering and Okhotsk plates, and the Komandorsky Island block.